(untitled) (Journal of Dhaka Medical College, 2021)
Objective: The present study was undertaken to assess liver function (using markers like SGPT, serum bilirubin, prothrombin time, serum albumin) in children suffering from Acute Lymphoblastic Leukemia. Materials & Methods: This study was carried out in the Department of Pediatric Hematology & Oncology, Dhaka Medical College Hospital, Dhaka, over a period 12 months from the day of approval of the protocol. All acute lymphoblastic leukaemia children admitted in Pediatric Hematology & Oncology Department in Dhaka Medical College Hospital and receiving chemotherapy of standard protocol for induction of remission were the study population. A total of outcome variable was hepatotoxicity resulting from chemotherapy given for induction of remission. Result: The mean age of the children was 4.4 years (range 2- 8 years). Males were a bit higher in the series with male to female ratio being 11:9. Liver function tests before therapy revealed that none of the children exhibited raised serum billirubin and only 2(4.5%) children had increased SGPT. However, 50% of the children had raised prothrombin and 43.2% had reduced serum . albumin. Liver function tests after therapy after induction of remission shows that 9(20.5%) children exhibited raised serum billirubin, the proportion of children with raised prothrombin remained almost same as before but the status of serum billirubin improved to some extent. However, proportion of children with raised SGPT was increased to 25%. Comparison of liver function in children after therapy during induction of remission with that before induction did not show any significant difference, except that the serum SGPT was significantly raised during induction of remission (p < 0.001). Conclusion: The study concluded that the current therapy for induction of remission of ALL cases does not produce any toxic effect on liver. Although, enzymes like SGPT take a sharp rise during induction of remission, it is transient and does produce any deleterious effect on liver. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 33-37